Metamorphoses of the Zoo: Animal Encounter after Noah - Acampora, Ralph R. (Lexington Books, 2010)
Metamorphoses of the Zoo: Animal Encounter After Noah is a volume dedicated to radically transformative approaches to spaces set aside as zoological parks or gardens. Historically, these establishments served as symbols of power and venues for entertainment, but today, they have taken to portraying themselves as flagships of environmental education, scientific research, and wildlife conservation. Along with the past century's turn in exhibition design toward increasingly naturalistic architecture, such portrayals have been received by many in an uncritically positive light. At the same time, it remains clear that zoos are immensely popular attractions, drawing hundreds of millions of visitors globally per year. This level of participation is consistent with the suggestion that humans harbor a strong sense of biophilia, one which moves them to seek out diverse life-forms when their own territories become too biologically homogenous; from such a vantage, it is no accident that zoos are most often situated in urban(izing) areas. Metamorphoses of the Zoo emphasizes creative and reconstructive analyses of zoos that do not simply advocate marginal reform or quick abolition. By focusing on issues such as interspecies progress and eco-psychological health, this unique collection will satisfy those in disciplines ranging from ecophilosophy to humanistic psychology to environmental studies.